Accountability of Notaries for Providing Covernotes in Credit Agreements - Musidah, Musidah (Jurnal Konstatering, 2022)
This study aims to understand and analyze the legal standing of covernotes made by a notary in a credit agreement and the responsibility of a notary for granting covernotes in a credit agreement which results in losses for banks. The approach method used in this study is sociological juridical, which is a method that is carried out by finding legal realities experienced in the field or an approach that stems from problems concerning matters that are juridical in nature or existing facts. The results of the study show that Covernote is not regulated in laws or positive laws in Indonesia. Publishing and drawing up covernotes by a notary has no legal basis. Covernotes are made based on a habit that can be accepted by society, so that it is trusted and considered as a binding legal product. Notaries carry out their responsibilities in making covernotes by checking and verifying first and ensuring the completeness of the required documents so as to minimize the potential for errors that can cause losses to banks. The notary's negligence in issuing a covernote whose contents contain statements or information that is not true causes him to be held legally responsible for his actions, namely criminal responsibility and civil responsibility.Keywords: Banks; Covernote; Responsibility.